(untitled) (Research, Society and Development, 2022)
As significant changes in smartphone technologies are being developed, new ways of working have been created, as well as several models of car service categories. However, these new forms of employment allowed flexible articulations in labor legislation, making it possible to make work precarious. The objective of this article is to analyze the new work relationships by application drivers, to highlight the precariousness of work faced by these professionals. This is a qualitative and explanatory study. Data collection took place through in-depth individual interviews carried out with ten application drivers in Mossoró - RN in 2021. The survey results show that the work of professionals can be characterized as precarious: they work long hours (also at night, weekends and holidays), they have low incomes (therefore increases the workload), lack social protection and also tend to work without a work contract.